THE LAST UNTAPPED RIVER IN UTAH: AN ARGUMENT AGAINST THE DEVELOPMENT OF THE BEAR RIVER (Utah Environmental Law Review; Vol 28 No 1 (2008), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The Bear River delivers over 1.2 million acre-feet , on average, to the Great Salt Lake each year. Because the Bear delivers a large amount of water, river Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 development has been studied since the 1950s, and the Bear is commonly referred to as "Utah‘s last untapped river." The Bureau of Reclamation identified several sites along the Bear River that would be optimal for damming and diversions to support municipal water usage over 60 years ago, but development did not begin in earnest until water shortages of the 1990s caused the issue of Bear River development to resurface when the Utah legislature passed the Bear River Development Act of 1991. According to several administrative documents, the state intends to make Bear water available within the next two decades, and it appears that the state will finally push forward to realize their 60 year old desire to tap the Bear.